Synthesis, Structure and Magnetic Property of a Tricapped Trigonal Prismatic TbIII-Based 3d-4f Complex. Issue 1 (March 2020) - Zhuang, Jia-Jia; Chen, Ming-Guang; Sun, Yan-Bing; Hang, Pei; Sui, Yang; Tong, Jia-Ping
Abstract: A novel 3d-4f Co II /Tb III cluster [Co6 Tb(Pic)6 O3 Cl3 ](H2 O)6 (1 ) (Pic = 2-Picolinic acid) has been synthesized and characterized via X-ray crystallographic and magnetic measurements. X-ray crystallographic and continued shape measurements analysis revealed that the central Terbium (III) is coordinated in TbO9 geometry with D 3 h symmetry. Magnetic studies indicated the complex presents a magnetic anisotropy with ferrimagnetic interactions.